Design of electronic differential system for an electric vehicle with In-wheel motor - Yıldırım, Merve; Öksüztepe, Eyyüp; Tanyeri, Burak; Kürüm, Hasan (My University, 2016)
This paper presents design of Electronic Differential System (EDS) for an Electric Vehicle (EV) with inwheel motor. EDS is generally used in EVs due to some drawbacks of mechanical differential such as being heavy systems and mechanical losses caused by the powertrains. According to the turning angle of the wheel, task of EDS for front wheels is to adjust rpm of the wheels. On the contrary for rear wheels, only rpm control is realized due to not steering. Hence, there are less studies on EDS for front wheels of EV in the literature. In this study, an EDS for front wheels of EV is designed. According to steering angle and speed of EV, the speeds of the front wheels are estimated by equations derived from Ackermann-Jeantand model using Codesys Software Package. The estimated speeds are sent to Induction Motor (IM) Drives via Controller Area Network-Bus (CAN-Bus). EDS is also simulated by Matlab/Simulink. Then, the speeds of the front wheels are experimentally measured by a tachometer. Codesys results are verified by both Simulink and experimental results. It is observed that the designed EDS is convenient for EVs with inwheel motor.
Bildiri - Yayımlanmamış
Keywords: Electric vehicle; In-wheel motor; Electronic differential system design